Wie es zu schaffen ist - Rüdiger Bachmann; David Baqaee; Christian Bayer; Moritz Kuhn; Andreas Löschel; Ben McWilliams; Benjamin Moll; Andreas Peichl; Karen Pittel; Moritz Schularick; Georg Zachmann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Ein Ende der Gaslieferungen aus Russland ist in letzter Zeit deutlich wahrscheinlicher geworden. Die russischen Liefermengen wurden bereits substantiell reduziert, und die Unsicherheit über künftige Lieferungen und die Versorgungslage im Winter ist groß. In dieser Studie fragen wir, was die ökonomischen Folgen eines kompletten Stopps russischer Gasimporte zum jetzigen Zeitpunkt (August 2022) wären. Seit unserer ersten Studie "Was wäre wenn" (Bachmann et al., 2022) zu den ökonomischen Effekten eines Importstopps für russische Energieträger aus dem März 2022 sind fast fünf Monate vergangen. Die durch die Studie ausgelöste Debatte hat den Blick für die Fragen und Annahmen geschärft, die für eine Einschätzung der wirtschaftlichen Kosten eines Importstopps russischer Energie entscheidend sind. In dieser Studie aktualisieren wir die Ergebnisse auf der Grundlage der Situation im August 2022.1 (i) Wir schätzen die notwendige Nachfragereduktion, die sich im Fall eines Stopps von russischen Gasimporten ab August 2022 ergeben würde und diskutieren wirtschaftspolitische Strategien, um diese Anpassung zu erreichen. (ii) Wir aktualisieren unsere Schätzung der zu erwartenden ökonomischen Kosten und diskutieren praktische Beispiele für Substitutionsmöglichkeiten im industriellen Bereich. (iii) Wir bewerten die wirtschaftspolitische Strategie der Bundesregierung, insbesondere die Entscheidung mit fortgesetzten Gasimporten aus Russland seit März 2022 die Speicherstände zu erhöhen, aber auf Maßnahmen zu einer frühzeitigen Reduzierung des Gasverbrauchs in der Stromerzeugung, in der Industrie und bei Haushalten und Gewerbe weitgehend zu verzichten. – – An end to gas supplies from Russia has recently become much more likely. Russian supply volumes have already been substantially reduced, and uncertainty about future supplies and the winter supply situation is high. In this study, we ask what the economic consequences would be of a complete halt to Russian gas imports at present (August 2022). Almost five months have passed since our first study, "What if" (Bachmann et al., 2022), on the economic effects of a March 2022 Russian energy import freeze. The debate sparked by the study has sharpened the focus on the issues and assumptions that are critical to estimating the economic costs of a Russian energy import freeze. In this study, we update the results based on the situation in August 2022. (i) We estimate the necessary demand reduction that would result if Russian gas imports were halted from August 2022 and discuss economic policy strategies to achieve this adjustment. (ii) We update our estimated expected economic costs and discuss practical examples of substitution options in the industrial sector. (iii) We evaluate the federal government's economic policy, in particular its decision to increase storage levels with continued gas imports from Russia since March 2022, but to largely forego measures to reduce gas demand in power generation, industry, and residential and commercial sectors. The key findings of the study can be summarized as follows: In the event of a complete loss of Russian gas supplies in the next few weeks, Germany will have to reduce its gas demand by around 25% (equivalent to 210 TWh) by the end of the coming heating period (April 2023), even if the planned liquefied natural gas terminals come on stream as planned in the winter. When factoring in the savings in gas demand that can be achieved through alternative energy sources in power generation, this leaves an adjustment of about 20% of gas consumption that must be borne by industry, households, businesses, and the public sector. Such a reduction is feasible in a collective effort if measures are taken quickly to save gas. The good news from our study is that Germany can get through the winter without Russian gas. Panic mongering is out of place. Nevertheless, it should be clear to everyone that the Russian invasion of Ukraine has made Germany permanently poorer. The days of cheap energy are over and collective efforts are needed to make the economy crisis-proof. Reducing gas consumption is feasible, but it comes at an economic cost. In particular, there is much less time now to substitute gas in the industrial sector and power generation than in the spring. It is difficult to estimate how many companies have made the sometimes costly investments in alternatives even without the appropriate political framework. However, it has become clear that the view that gas substitution was not possible at all within six months was wrong. There are now numerous examples of substantial substitution possibilities, including in the chemical and glass production industries. The bottom line is that the economic costs of adjusting to an import freeze are likely to remain similar to those of committing to an import freeze already in the spring. This is because the gas gap is smaller than in the spring, but the remaining adjustment period is shorter. In this respect, the costs remain substantial, but manageable with appropriate economic policy measures. There is no threat of mass poverty or popular uprisings in the event of a halt to Russian gas imports. The economy will face production losses of a magnitude that Germany has already managed in the past when it had to face economic shocks. It is also important to interpret the effects of a gas import stop relative to a scenario without an import stop. For example, Germany could fall into recession even without an import freeze. The assessment of the German government's strategy of not enforcing an early demand adjustment and continuing gas imports from Russia despite the war of aggression on Ukraine is ambivalent. Although a good 100 TWh of gas was stored from April to July, without Russian supplies the need for adjustment on the demand side remains substantial at 25% until the end of the next heating period. In a counterfactual scenario, in which Germany would have had to manage without Russian gas imports as early as from April onwards, demand would have had to be reduced by 31%, a good 6 percentage points more. Yet in return, there would have been more time to prepare the appropriate adjustments for the winter heating period. Even if the storage facilities were filled to 100% in the fall, Germany would remain dependent on Russian imports for normal winter consumption and would thus remain vulnerable to blackmail from Moscow. This is because the storage facilities only have a total capacity of below 250 TWh, which is roughly equivalent to the consumption of two winter months. In this respect, the focus on storage levels and the neglect of adaptation measures was not suitable to end Germany's dependence on Russia and its political blackmail ability completely and quickly. While closer cooperation with European partners could have mitigated the necessary reduction in gas demand in Germany, there is still a risk that national go-it-alone efforts will undermine essential European energy solidarity. In any case, the BMWK's efforts to build LNG terminals and diversify gas supplies through imports from third countries are positive. However, this could have been done even with an import freeze or tariff solutions in March.
Keywords: 330